History of Sufism and its Scientific and Methodological Foundations (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the fact that the philosophy of Sufism, which has gained great importance in the history of mankind, is one of the spiritual values, in particular, the uniqueness of the Kubroviya, Yassawi and Naqshbandi sects, the general and various aspects of their spiritual values, scientifically and philosophically different.